Stochastic polynomial optimization. (3rd March 2020) - Nie, Jiawang; Yang, Liu; Zhong, Suhan
ABSTRACT: This paper studies stochastic optimization problems with polynomials. We propose an optimization model with sample averages and perturbations. The Lasserre-type Moment-SOS relaxations are used to solve the sample average optimization. Properties of the optimization and its relaxations are studied. Numerical experiments are presented.